Pseudoelasticity And Cyclic Behaviours Of Nickel-Rich NiTi Shape Memory Alloy - Hishamiakim, Mohamad (2019)
Near-equiatomic NiTi is one of the famous shape memory alloys used in vibration isolation and dampening application. This is due to its pseudoelastic behaviour. Pesudoelasticity refers to the ability of shape memory alloy to instantly recover from very large deformation after the deformation load is released. However, the yield strength of this alloy is low thus susceptible to localized dislocation. In this regard, preserving the pseudoelasticity of the alloy becomes a challenge. The alloy degrades, involving progressive accumulation of residual strain and reduction of the transformation stress when subjected to cyclic loading. Aging treatment is widely used to improve the yield strength of the alloy through precipitation hardening. Only coherent precipitates can profoundly increase the yield strength. Also, the precipitation is more effective in high Ni content of NiTi alloy. The effect of ageing on the yield strength and functional fatigue resistance are less explored especially for composition above 51at%Ni. This study aims to quantify the ageing effect of Ni-rich NiTi alloy towards the yield strength and the pseudoelastic behavior. The response of the yield strength towards the cyclic performance of Ni-rich NiTi alloys is also investigated. Commercial Ni-rich NiTi alloys with composition Ti-51at%Ni and Ti 50.8at%Ni were used in this study. The experimental works involved the isothermal ageing at a temperature range of 400°C to 550°C for 15, 30 and 60 minutes after solution treated at 900°C. Thermal analysis was done using Differential Scanning Calorimetry (DSC) to specify the phase transformation temperature. The tensile tests at room temperature were carried out to characterise the pseudoelasticity, yield strength and the cyclic performance using universal tensile machine (UTM). The results show that the yield strength increased as the ageing temperature increased, and the specimen of 51at%Ni alloy aged at 450°C for 30 minutes recorded the highest martensite yield stress value. Ageing at above 500°C caused the yield strength to decrease significantly. By comparison, 50.8at%Ni specimens showed lower yield strength than 51at%Ni. The pseudoelasticity of the aged specimens was found to decrease with the increase of ageing times. NiTi alloy with 51at%Ni showed less than 1% unrecovered strain at room temperature even though the austenite finish temperature, Af is higher than the testing temperature. Unlike 51at%Ni, 50.8at%Ni specimens aged at 425°C to 500°C showed poor recoverability with more than 2% residual strain. The cyclic deformation behaviour of the 51at%Ni alloy was found to be more stable for specimen aged at lower ageing temperature. Ageing at very high temperature (525°C and 550°C) caused the residual strain to increase and the transformation stress to decrease significantly over the first few cycles indicating functional behaviour degradation. Ageing of Ti-51at%Ni at 450°C for 30 minutes is recommended as the best ageing condition for cyclic deformation purpose. It produced the highest martensite yield stress, σyM of 1335 MPa, performing considerably good pseudoelasticity with residual strain, εr of 0.41% and high functional fatigue resistance with residual strain difference, ∆εr of 0.08%.